The science and technology in the formation the student of Physical Culture (Original) (Revista científica Olimpia, 2021)
This research work deals about the importance of science and technique in the initial formation of the Physical Culture professional with a focus related to games for the labor in the Program Educa tu Hijo in the physical activity that children develop. The objective shows a trend towards appreciating the scientific impact and the technology in the focus related to games of the student of Physical Culture. Different theoretic methods were used such as, the analysis and synthesis, and the systemic - structural to structure actions and as empiric method: the observation. These actions will make possible the raising of the students´ knowledge on the physical activity in the Program Educa tu Hijo.
Keywords: initial formation; games formation; focus related to games; Physical Culture; science; technology